RANCANG BANGUN ALAT SHAKER DENGAN INPUT MENGGUNAKAN KEYPAD BERBASIS ARDUINO - Pauzi, Gurum Ahmad; Septiani, Elsyana; Suciati, Sri Wahyu; Supriyanto, Amir (Journal of Energy, Material, and Instrumentation Technology, 2024)
This study aims to develop an orbital shaker device with an Arduino Uno-based input system for rpm and time, utilizing a keypad as the input medium. The orbital shaker is designed to homogenize chemical solutions through circular motion, featuring display functions for rpm and mixing time. The device uses a NEMA 17 stepper motor as the main motor, a 4x4 membrane keypad for input, an Arduino Uno as the processor, and a TM1637 display for rpm and time readings. Testing of the orbital shaker includes calibration of rpm and time. Rpm calibration is performed using a laser tachometer to measure the conformity of the inputted rpm values, while time calibration uses a stopwatch to determine system error values. The rpm calibration results indicate an average error rate of 0.36%, with an accuracy of 99.62% and precision of 99.58%. In comparison, time calibration results show an average error rate of 0.15%, with an accuracy of 99.84% and precision of 99.88%. Further rpm measurements were conducted with solution loads ranging from 100 to 1000 g, increasing in increments of 100 g, and rpm testing was performed from 100 to 500 rpm. The test results demonstrate that the optimal performance of the designed orbital shaker occurs at rpm values between 100 and 450 with a load range of 100–600 g.